Controlling the interaction of hemicellulose (galactoglucomannan, GGM) with cellulose by means of enzyme modification - Professor Tommy Nylander; Dr Andrew Caruana; Dr Alexei Vorobiev; Ms Polina Naidjonoka; Dr Gunnar Palsson (ISIS Facility, 2019)
Softwood hemicellulose (galactoglucomannan, GGM) is one of the major plant polysaccharides found in cell walls after cellulose. It makes up to 25% of the wood in Sweden, however, currently most of it is obtained as a by-product of several industrial processes and discarded in waste-stream. The aim of the project is to develop sustainable processes to biocatalytically modify GGM structure in order to transform it to a versatile and excellent renewable resource for novel high-performance products. One of such products is a coating material for wood, therefore adhesion properties of GGM to cellulose are of great interest. The focus of the present study is the influence of size and galactose substitution degree on adsorption of GGM to cellulose surface.
Keywords: STFC ISIS Neutron and Muon Data